As hipermulheres: cinema e ritual entre mulheres, homens e espíritos - Bernard Pêgo Belisário (2014)
This dissertation proposes an approach towards the film The Hyperwomen (2011), a result of a partnership between the indigenous filmmaker Takumã Kuikuro, the anthropologist Carlos Fausto and the former Video in the Villages project's instructor, Leonardo Sette. This approach consists in three analytical movements. The first one intents to characterize the manner in which the film enmeshes fictional procedures in its documentary mise en scène. The second one investigates the relationship between the camera and the filmed people during the ritual performances, considering music as an engine for these ritual-filmic scenes. The third movement starts from the native cosmological category itseke (animal-spirit) to analyze the three moments in which these forces are evoked in the film. For these analyzes, we developed a methodology that articulates concepts from the cinema/communicational studies, ethnographic/ethnomusicologic information and a brief field research.